Investigation of Capital Market Efficiency in Indonesia - Gita Masria Hutapea; Ahmad Fauzan Fathoni; Yulia Efni (AFEBI Management and Business Review, 2019)
In the midst of a national economic growth downturn that affected the capital market as a subsystem of the economy, now Indonesia capital market industry began to look at the development of the application of the principles of sharia as an alternative investment instruments in capital markets activities in Indonesia. The growth of the Islamic capital market in Indonesia is quite encouraging, but the Islamic capital market exposure is still minimal. Lack of public understanding about the Islamic capital market into doubt for investors to invest in the capital market. With the background of the problem, this research aims to investigate the level of efficiency increase of capital markets in Indonesia to see the influence of the capital market and the asymmetry of information on abnormal return. The population in this study are all listed company listed on the Stock Exchange 2014-2018 period as many as 626 companies with a total sample of 238 companies were selected based on criteria predetermined. The analytical method used in this research is multiple linear regression and the results showed that the type of capital markets significant negative effect on abnormal returns and the information asymmetry significant positive effect on abnormal returns. The continued development of the Islamic capital market information asymmetry and abnormal returns are also lower so the efficiency of the capital market has also increased. The analytical method used in this research is multiple linear regression and the results showed that the type of capital markets significant negative effect on abnormal returns and the information asymmetry significant positive effect on abnormal returns. The continued development of the Islamic capital market information asymmetry and abnormal returns are also lower so the efficiency of the capital market has also increased. The analytical method used in this research is multiple linear regression and the results showed that the type of capital markets significant negative effect on abnormal returns and the information asymmetry significant positive effect on abnormal returns. The continued development of the Islamic capital market information asymmetry and abnormal returns are also lower so the efficiency of the capital market has also increased.